2006
DOI: 10.1590/s1806-37132006000800005
|View full text |Cite
|
Sign up to set email alerts
|

Doenças das vias aéreas superiores

Abstract: Um dos principais objetivos deste capítulo é alertar os profissionais da saúde, em especial os pneumologistas, médicos do trabalho e clínicos gerais, sobre as repercussões para o aparelho respiratório decorrentes das agressões das vias aéreas superiores por exposição ocupacional.Uma grande diversidade de agentes ambientais e ocupacionais pode causar doenças nas vias aéreas superiores. Entre as principais funções das vias aéreas superiores, destacamos: a de filtro, removendo agentes infecciosos, alérgicos e tóx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
(4 reference statements)
1
9
0
3
Order By: Relevance
“…These data differ from those from other studies, which reported that the length of exposure to agents in the work environment is related to the presence of respiratory symptoms and of changes in lung function. (2,6,12) In the present study, the occupational exposure factors (dust and chemical product) were shown to be associated with the presence of general respiratory symptoms. The workers who reported inhaling dust during their work hours were 12.4 times more likely to present with general respiratory symptoms than were those who reported not having inhaled dust.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…These data differ from those from other studies, which reported that the length of exposure to agents in the work environment is related to the presence of respiratory symptoms and of changes in lung function. (2,6,12) In the present study, the occupational exposure factors (dust and chemical product) were shown to be associated with the presence of general respiratory symptoms. The workers who reported inhaling dust during their work hours were 12.4 times more likely to present with general respiratory symptoms than were those who reported not having inhaled dust.…”
Section: Discussionsupporting
confidence: 48%
“…(17) Exposure to petroleum derivatives can affect the airways in various ways, depending on the physical, chemical, and biological properties of the pollutants that are formed; the size/concentration of the particles inhaled and concomitant exposure can be risk factors for various diseases, such as asthma, sinusitis, rhinitis, perforation of the nasal septum, and altered sense of smell. (2,18) general respiratory symptoms than were those who did not. Contact occurs when the product is used to lubricate the molds of the machines that shape the tiles or when the agent combusts after having been heated by the machine plates, releasing in the air numerous toxic substances (products derived from the combustion of the petroleum derivative), (14) which enter the airways directly, because most of the workers do not use respiratory protection equipment while at work.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Apresentando como consequência da exposição prolongada, uma rinite alérgica (qualquer inflamação na mucosa nasal), representando este um problema de extensão mundial (BAGATIN; COSTA, 2006).…”
Section: Danos a Saúde Humanaunclassified
“…Sua incidência na população é alta, e sua prevalência só é menos significativa que as rinites virais. A rinite alérgica representa, hoje, problema de extensão mundial, com tendência a se agravar cada vez mais, em virtude do progresso industrial, com o surgimento crescente de novas substâncias alergênicas, aumento das grandes concentrações urbanas e da poluição ambiental (BAGATIN;ANDRADE DA COSTA, 2006). Em cães a rinite alérgica tem sido considerada doença, porém, ainda pouco estabelecida .…”
Section: Rinite Inflamatóriaunclassified